Worldwide productivity and research trends of publications concerning stent application in acutely ruptured intracranial aneurysms: A bibliometric study - Chen, Rundong; Wei, Yanpeng; Zhang, Guanghao; Zhang, Renkun; Zhang, Xiaoxi; Dai, Dongwei; Li, Qiang; Zhao, Rui; Xu, Yi; Huang, Qinghai; Yang, Pengfei; Zuo, Qiao; et al. (Frontiers in Neurology, 2022)
BACKGROUND: Stenting is a common clinical practice to treat acutely ruptured intracranial aneurysm (RIA). Although multiple studies have demonstrated its long-term safety and effectiveness, there is currently a lack of bibliometric analysis on stent application in acutely RIA. This study sought to summarize the current status of research in this field and lay a foundation for further study. MATERIALS AND METHODS: Related publications were searched in the Web of Science Core Collection (WoSCC) database. Data analysis and visualization were performed by R and CiteSpace software. RESULTS: Included in this study were 275 related articles published in English from 1997 to 2022. The number of publications showed a ﬂuctuating ascending trend. The reference co-citation network identified 13 clusters with a significant network (Q=0.7692) and convincing clustering (S=0.9082). The research focus was aneurysmal SAH and the application of stents during interventional procedures. The main trends of research were: 1) development of materials, and 2) safety of stent application in acutely RIA. The United States contributed the most articles, and Jianmin Liu was the most proliﬁc author. Mayo Clinic was the leading institution in this field. Most articles were published in Interventional Neuroradiology. CONCLUSIONS: This study analyzed the research trends, hotspots and frontiers of stent application in acutely RIA. It is our hope that the results obtained could provide useful information to researchers to get a clearer picture about their future research directions in this field.